Peran Pendampingan Pastoral Melalui Permainan Indoor dalam Mengurangi Kesepian Lansia di Panti Lanjut Usia Lydia Tomohon - Luas, Luosje Treesje; Manumpil, Michael Calvyn Alfrits; Towoliu, Gerry; Ering, Sion (Educatio Christi, 2025)
Loneliness is a serious problem for older people, and can have a negative impact on their mental and physical health. Many of them experience feelings of isolation due to the loss of family and social environment, let alone living and settling in a retirement home or nursing home. A qualitative study was conducted to explore the role of pastoral care in addressing this loneliness. The research involved in-depth interviews and participatory observation with 5 elderly people who participated in the pastoral care program, as well as nursing home staff and assistants. The results showed that pastoral care not only reduced loneliness, but also improved their quality of life through stronger social relationships. This study is important because it incorporates spiritual and emotional aspects in the context of pastoral care, and prioritizes the experiences of older adults as an important element in understanding social support in Lydia's elderly home. The findings have the potential to provide recommendations for the development of a more effective pastoral care program, which could ultimately improve the well-being of the elderly in Lydia Tomohon.